The Relationship Between Risky Behaviors, Individual Characteristics, and Sexual Revictimization Among College Women - Mummert, Sadie J. (2010)
Sexual revictimization of college women is a relatively new area of study within the field of victimology. Although the link between childhood sexual assault (CSA) and adult revictimization has been examined, many aspects of why college-aged females are revictimized have gained little attention. This Master’s thesis will explore the current literature as well as analyze the possible link between risky behaviors, individual characteristics, and sexual revictimization. Using Jacquelyn W. White and Paige Hall Smith’s (2004) data, A Longitudinal Perspective on Physical and Sexual Intimate Partner Violence Against Women, bivariate analyses were conducted regarding the revictimization of college women. The findings suggest a few differences between single victims and revictims. The findings also suggested that nonvictims and revictims were found to have multiple differences across variables. Suggestions for future research will be discussed